2015
DOI: 10.1016/j.ejbt.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a suppressive subtractive hybridization library of Alternaria alternata resistant to 2-propenyl isothiocyanate

Abstract: Background: Isothiocyanates (ITCs) are natural products obtained from plants of the Brassicas family. They represent an environmentally friendly alternative for the control of phytopathogenic fungi. However, as it has been observed with synthetic fungicides, the possibility of inducing ITC-resistant strains is a major concern. It is, therefore, essential to understanding the molecular mechanisms of fungal resistance to ITCs. We analyzed a subtractive library containing 180 clones of an Alternaria alternata str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The strain’s ability to grow was restored from complete inhibition to 80–85% growth speed at the highest allyl ITC dosage, accompanied by induction of glutathione S-transferase-like genes, and a 2-fold increase in glutathione S-transferase catalytic activity, suggesting a specific detoxification mechanism. An interesting study of the transcriptome of an allyl ITC-resistant Alternaria alternata strain by [ 131 ] has concluded that allyl ITC can induce tolerance/resistance mechanisms in the same manner as synthetic fungicides. Induced genes coding similar-to-known proteins included many proteins and enzymes involved in the activation of signal cascades promoting cell repair and maintenance, the overexpression of which result in generic resistance-like traits.…”
Section: Proposed Mechanisms Of the Isothiocyanate Antifungal Activitymentioning
confidence: 99%
“…The strain’s ability to grow was restored from complete inhibition to 80–85% growth speed at the highest allyl ITC dosage, accompanied by induction of glutathione S-transferase-like genes, and a 2-fold increase in glutathione S-transferase catalytic activity, suggesting a specific detoxification mechanism. An interesting study of the transcriptome of an allyl ITC-resistant Alternaria alternata strain by [ 131 ] has concluded that allyl ITC can induce tolerance/resistance mechanisms in the same manner as synthetic fungicides. Induced genes coding similar-to-known proteins included many proteins and enzymes involved in the activation of signal cascades promoting cell repair and maintenance, the overexpression of which result in generic resistance-like traits.…”
Section: Proposed Mechanisms Of the Isothiocyanate Antifungal Activitymentioning
confidence: 99%
“…ITCs readily attack thiols and amines, consequently modifying proteins and disrupting biochemical processes, which play an important role in the defense mechanisms of GSL-containing plants against infectious microorganisms or predators . Some organisms developed tolerance mechanisms during evolution to adapt to stress; for example, some pathogens that colonize plants of the order Brassicales possess tolerance to ITC toxicity; of note, the ability to detoxify ITCs via ITC hydrolases, the glutathione conjugation pathway, or active efflux has been discovered in these organisms. Myrosinase-producing organisms can actively release ITCs from GSLs and, therefore, should possess the mechanism(s) to tolerate the ITCs generated. However, tolerance of the strains to ITCs has not been well investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In actively growing plants, high N availability speeds up primary metabolism and plant growth, while in plants with arrested growth improved nutrition can enhance storage and secondary metabolism 16 , 17 . Nitrogen is needed for the biosynthesis of glucosinolates (GLS), the anti-herbivore toxins found in the Brassica family, and their volatile derivatives isothiocyanates (emitted after tissue damage) mediate plant–insect interactions 18 20 . Since specialist herbivores can orient towards GLS 21 , high N in crops can even benefit pests 22 25 .…”
Section: Introductionmentioning
confidence: 99%